Brightness enhancement film
By using low-refractive index coatings and hollow nanoparticles in the brightening film, combined with an integrated forming design and a double-prism layer structure, the cost and environmental problems of the existing brightening films when improving brightness are solved, and the effects of high brightness, high wear resistance and excellent stability are achieved.
Patent Information
- Application Number
- CN202421368686.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2034-06-17
AI Technical Summary
The existing brightness enhancement films face high production costs, environmental impacts and poor optical performance when improving brightness, especially the impact of fluoride materials on the environment and interference fringes caused by excessive prism structure.
A low refractive index coating is used, with hollow nanoparticles of a specific diameter range interspersed in the middle, and through an integrated substrate layer, coating and prism layer design, combining the biprism layer structure with different prism extension directions and top angles, the size and weight ratio of the hollow nanoparticles are optimized.
It effectively reduces the reflectivity of the brightening film, improves the light transmittance, significantly improves the brightness, and enhances the hardness and wear resistance of the back coating, avoids high-temperature calcination and fluoride use, and reduces production costs.
Smart Images

Figure CN222671983U_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical films, and in particular to a brightness enhancement film. Background Art
[0002] Brightness enhancement film is a transparent optical film, which is mainly used to improve the luminous efficiency and brightness of light sources. It consists of a three-layer structure, including a back coating, a transparent substrate layer and a microprism layer. When light passes through the brightness enhancement film, after refraction, total reflection and light accumulation, the originally scattered light is concentrated and directed to the front, while the unused light outside the viewing angle is recycled, thereby reducing light loss. This technology makes brightness enhancement film widely used in display screens, automotive surface coverings, home decoration and construction, which not only improves the brightness and uniformity of the product, but also enhances the aesthetics and durability. Among them, the composite brightness enhancement film (POP) further improves the assembly efficiency and brightness by bonding two brightness enhancement films into one, becoming an efficient optical solution.
[0003] The existing brightness enhancement methods of brightness enhancement films usually rely on increasing the refractive index of the prism layer glue or increasing the prism structure. However, both methods face some challenges and limitations. First, although the use of high refractive index materials as prism layer glue can improve brightness, the price of high refractive index materials is often expensive, which increases production costs. Secondly, increasing the prism structure requires the use of more coatings, which will also increase costs. Moreover, a prism structure that is too large can easily cause interference fringes, which in turn affects the quality of the picture, such as causing adverse visual effects or dispersion problems.
[0004] To overcome these limitations, the industry has begun to explore new solutions. One innovative approach is to introduce a low-refractive-index coating on the back of the brightness enhancement film. This coating improves the light transmission efficiency of the backlight source by the difference in refractive index with the internal structure of the brightness enhancement film, thereby improving the overall optical benefit of the brightness enhancement film. However, this method usually uses fluoride as a low-refractive coating. Although effective, fluoride has a certain impact on the environment, which requires special consideration of its environmental friendliness and sustainability when used. Therefore, future research and development will focus more on reducing the impact on the environment while improving brightness, as well as finding more cost-effective solutions. Utility Model Content
[0005] The purpose of the present application is to provide a brightness enhancement film with low production cost and high efficiency, which avoids the use of fluoride and high-temperature calcination, and does not require a moth-eye structure that is difficult to produce, has poor wear resistance and is easily scratched. A brightness enhancement film of the present application includes a first substrate layer, a low refractive index coating and a first prism layer;
[0006] The first prism layer is disposed on the front side of the first substrate layer;
[0007] The low refractive index coating is disposed on the back side of the first substrate layer;
[0008] Wherein, hollow nanoparticles are mixed in the low refractive index coating, and the diameter of the hollow nanoparticles ranges from 20 to 500 nm.
[0009] In one embodiment, the thickness of the low refractive index coating layer is smaller than the thickness of the first substrate layer.
[0010] In one embodiment, the second substrate layer and the second prism layer are further included. The second substrate layer is disposed on a surface of the first prism layer opposite to the first substrate layer, and the second prism layer is disposed on a surface of the second substrate layer opposite to the first prism layer.
[0011] In one embodiment, an extending direction of the prisms in the first prism layer is different from an extending direction of the prisms in the second prism layer.
[0012] In one embodiment, the top angles of the prisms in the first prism layer and the second prism layer are 90°.
[0013] In one embodiment, the size of the hollow structure in the hollow nanoparticles remains unchanged.
[0014] In one embodiment, the low refractive index coating has a thickness ranging from 0.1 to 25 μm.
[0015] Compared with the prior art, the present application has the following beneficial effects: the brightness enhancement film of the present application includes a substrate layer, a prism layer and a back coating, wherein hollow nanoparticles are mixed in the back coating, and by optimizing the diameter range and weight ratio of the hollow nanoparticles, the reflectivity of the incident surface of the brightness enhancement film can be effectively reduced, the light transmittance can be improved, and the brightness of the brightness enhancement film can be improved. The use of hollow nanoparticles also enhances the pencil hardness and wear resistance of the back coating of the brightness enhancement film, making it more durable. In further technical optimization, the present application further optimizes the scheme, including an integrally formed substrate layer, coating and prism layer, and a double prism layer design with different prism extension directions and vertex angles, to improve the performance of the brightness enhancement film and increase the flexibility and diversity of its design. In addition, the present application further optimizes the performance of the brightness enhancement film and improves the performance and stability of the brightness enhancement film by controlling parameters such as the size of the hollow nanoparticles, the size of the hollow structure, and the thickness of the low refractive index coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a schematic structural diagram of a brightness enhancement film in a specific embodiment of the present application;
[0017] Figure 2 It is a schematic structural diagram of a brightness enhancement film in another specific embodiment of the present application.
[0018] Explanation of reference numerals: 100, first substrate layer; 200, low refractive index coating layer; 300, first prism layer; 400, second substrate layer; 500, second prism layer. DETAILED DESCRIPTION
[0019] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0021] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0022] See also Figure 1 , Figure 1 1 is a schematic diagram of the structure of a brightness enhancement film in a specific embodiment of the present application. The brightness enhancement film in a preferred embodiment of the present application reduces the reflectivity of the light incident surface of the brightness enhancement film, improves the light transmittance, and thereby improves the brightness of the brightness enhancement film, while improving the pencil hardness and wear resistance of the back coating of the brightness enhancement film. The brightness enhancement film includes a first substrate layer 100, a low refractive index coating 200 and a first prism layer 300. The first substrate layer 100 serves as the basis of the entire brightness enhancement film and provides the necessary mechanical strength and stability. It is usually made of a material with stable optical properties and good light transmittance to ensure that light will not be excessively attenuated or scattered when passing through.
[0023] The low refractive index coating 200 is arranged on the back of the first substrate layer 100, and hollow nanoparticles are mixed in the low refractive index coating 200, and the diameter of the hollow nanoparticles ranges from 20 to 500 nm. The low refractive index coating 200 is arranged on the back of the first substrate layer 100, and the refractive index is lower than that of the substrate layer, which helps to reduce the reflection loss of light, thereby improving the transmittance of light. The low refractive index coating 200 is mixed with hollow nanoparticles, and the diameter of the nanoparticles is precisely controlled within the range of 20 to 500 nm. Such a size design enables them to effectively scatter light of a specific wavelength. Through this structural design, the brightness enhancement film can reduce reflection and scattering losses while maintaining efficient light transmission, thereby significantly improving the brightness and visual experience of the screen.
[0024] The first prism layer 300 is arranged on the front side of the first substrate layer 100, and its structure consists of a series of tiny prisms. These prisms can effectively converge and guide the light passing through the brightness enhancement film to further improve the brightness and clarity of the screen. The design angles and spacings of the prisms are precisely calculated to achieve the best optical effect.
[0025] In order to optimize the manufacturing process of the brightness enhancement film, the first substrate layer 100, the low refractive index coating 200 and the first prism layer 300 are formed in one piece. The one-piece forming means that each layer will be a whole without obvious gaps and there are no other material layers between the layers. The design of integrated forming not only improves the overall performance of the brightness enhancement film, optimizes the production process and improves production efficiency, but also ensures the close combination of the layers, avoids the loss of optical performance due to the difference between the materials, and the interface state between different layers has an important influence on the transmission and reflection of light. A stable interface is formed between the first substrate layer 100, the low refractive index coating 200 and the first prism layer 300, which reduces the scattering and reflection of light, thereby improving the brightness of the brightness enhancement film, and having better durability and stability. Due to the close combination between the layers, the separation or shedding of the layers caused by the external environment or the use time is avoided. The one-piece forming method forms a whole. During the manufacturing process of the brightness enhancement film, the continuous coating and curing of each layer can be realized through a continuous production line, which can not only ensure the close combination between the layers, but also accurately control the thickness and uniformity of each layer.
[0026] For the structure of hollow nanoparticles, the diameter of the hollow structure in the hollow nanoparticles is 30%-85% of the diameter of the hollow nanoparticles. The hollow nanoparticles mixed in the low refractive index coating 200 not only have a specific diameter range, but also the hollow structure inside is designed. The diameter range design of the hollow structure can also affect the optical performance of the brightness enhancement film. By adjusting the diameter of the hollow structure, the refractive index of the nanoparticles can be changed, thereby affecting the transmittance and reflectivity of the brightness enhancement film to light. When the diameter of the hollow structure is within the range of 30%-85% of the diameter of the nanoparticles, a more ideal refractive index value can be obtained, so that the brightness enhancement film has better optical performance. In addition, the added weight ratio range of the hollow nanoparticles in the low refractive index coating 200 is controlled within the range of 30%-50%.
[0027] To further improve the display effect of the brightness enhancement film, please refer to Figure 2 , Figure 2 : is a schematic diagram of the structure of a brightness enhancement film in another specific embodiment of the present application, which also includes a second substrate layer 400 and a second prism layer 500, wherein the second substrate layer 400 is arranged on the surface of the first prism layer 300 relative to the first substrate layer 100, and the second prism layer 500 is arranged on the surface of the second substrate layer 400 relative to the first prism layer 300. The design of the double prism layer improves the optical performance of the brightness enhancement film, and the prism structure in the first prism layer 300 and the second prism layer 500 can converge and guide the light twice, further reducing the scattering and loss of light, thereby significantly improving the brightness and clarity of the screen. By adjusting the parameters such as the extension direction and vertex angle of the prisms in the first prism layer 300 and the second prism layer 500, different optical effects and functions can be achieved. When the vertex angle of the prism in the first prism layer 300 is greater than the vertex angle of the prism in the second prism layer 500, the brightness enhancement film can have a higher brightness gain in a specific direction; and when the prisms of the two prism layers extend in different directions, effective convergence and guidance of light in different directions can be achieved.
[0028] Specifically, the extension direction of the prisms in the first prism layer 300 is different from the extension direction of the prisms in the second prism layer 500. In a further optional technical solution, the prism vertex angle in the first prism layer 300 is greater than the prism vertex angle in the second prism layer 500, and the light is further made uniform by different prism vertex angles.
[0029] Specifically, the top angle of the prisms in the first prism layer 300 and the second prism layer 500 is 90°. When the top angle of the prism is 90°, the prism structure is easier to control and the optical path design is more regular. In another optional technical solution, the top of the prism can be selected to be curved. The prism design with a curved top helps to optimize the refraction and reflection of light. Compared with traditional straight or flat prisms, the curved prism can better refract and guide the incident light, reducing the loss and waste of light. The curved prism can transmit light in a smoother and more uniform manner through its special shape, reducing unnecessary reflection and refraction, thereby reducing the occurrence of glare and ghosting. The curved prism design can also enhance the three-dimensional sense and depth of the displayed image.
[0030] In order to further optimize the display effect of the brightness enhancement film, the size of the hollow nanoparticles in the low refractive index coating 200 gradually increases in the direction away from the first substrate layer 100. In the low refractive index coating 200, the size of the hollow nanoparticles gradually increases, so that the refractive index distribution inside the coating presents a gradient change. Since the refractive index is related to the density of the material and the size of the refractive index material, this gradient change can effectively reduce the sudden change of the refractive index of light when passing through the coating, thereby reducing the reflection and scattering of light. As the size of the nanoparticles gradually increases, the stress distribution inside the coating will also change accordingly. This change can reduce the stress concentration phenomenon inside the coating, thereby improving the toughness and scratch resistance of the coating. The design that the size of the hollow nanoparticles in the low refractive index coating 200 gradually increases in the direction away from the first substrate layer 100 can not only effectively reduce the refractive index of light, enhance the mechanical properties of the coating, and optimize the surface flatness of the coating.
[0031] Specifically, the size of the hollow structure in the hollow nanoparticles remains unchanged, and volume expansion is a technical problem. The use of hollow nanoparticles with a constant hollow structure size can provide a fixed space to buffer the volume expansion during use, thereby preventing the volume changes of hollow nanoparticles with different hollow structures, thereby avoiding the material breakage and fracture caused.
[0032] Specifically, the thickness of the low refractive index coating is in the range of 0.1-25 μm. In a further preferred embodiment, the thickness of the low refractive index coating is in the range of 0.1-5 μm.
[0033] Specifically, the low refractive index coating 200 includes at least two low refractive index sublayers, and the size of the hollow nanoparticles in the low refractive index sublayers gradually increases in the direction away from the first substrate layer 100. The gradually increasing hollow nanoparticles can ensure the wear resistance of the outermost layer, and by adjusting the size change, the optical properties of the brightness enhancement film are not affected internally.
[0034] In addition, in order to further improve the stability, the surface of the hollow nanoparticles in the low refractive index coating 200 is coated with an antistatic resin. By introducing the antistatic resin, the surface resistance of the hollow nanoparticles can be further reduced, thereby significantly enhancing the antistatic performance of the coating. The wrapping effect of the antistatic resin can also improve the adhesion between the hollow nanoparticles and the coating matrix, thereby enhancing the stability and durability of the coating, helping to reduce problems such as coating shedding and cracking caused by the external environment or increased use time, thereby ensuring the stability and reliability of the coating during long-term use.
[0035] The brightness enhancement film of the present application is described in detail below with multiple specific production steps, mainly including obtaining different coating reflectances by blending different proportions of nano hollow low-refractive microbeads, using this coating to make brightness enhancement films respectively, and studying the corresponding performances to obtain a better specific implementation method. The specific tests include: 1. Using ATAGO's RX-9000α refractometer to test the refractive index of the back coating; 2. Using Sanens' TS8296 spectrophotometer to test the 550nm reflectivity and haze of the back coating; 3. Using a Mitsubishi pencil hardness tester to test the pencil hardness of the back coating, with a load of 500g; 4. Using a wear-resistant testing machine, use a diffusion film to rub the back coating from the front, and record the load that can withstand 5 frictions; 5. Using Topcon's BM-7A to test the brightness of the brightness enhancement film sample.
[0036] The specific preparation method of the low-fold back coating brightness enhancement film is as follows: use 50% to 70% by weight of acrylic monomer, 1% to 5% by weight of photoinitiator, and 0.1% to 1% by weight of leveling and lubricating agent (BYK company model BYK-333) as a coating liquid; add hollow nanoparticles with a diameter of 20 to 500 nm and a weight of 30 to 50% to the coating liquid and mix evenly; apply the obtained mixed coating liquid to one side of the substrate; use ultraviolet curing to cure the coating; and then prepare a prism structure on the other side of the substrate to make it a brightness enhancement film.
[0037] Example 1
[0038] The diameter of the hollow nanoparticles is selected to be 20 nm, and the addition ratio of the hollow nanoparticles is 30% by weight.
[0039] Example 2
[0040] The diameter of the hollow nanoparticles is selected to be 20 nm, and the addition ratio of the hollow nanoparticles is 50% by weight.
[0041] Example 3
[0042] The diameter of the hollow nanoparticles is selected to be 50 nm, and the addition ratio of the hollow nanoparticles is 30% by weight.
[0043] Example 4
[0044] The diameter of the hollow nanoparticles is selected to be 100 nm, and the addition ratio of the hollow nanoparticles is 30% by weight.
[0045] Example 5
[0046] The diameter of the hollow nanoparticles is selected to be 500 nm, and the addition ratio of the hollow nanoparticles is 30% by weight.
[0047] Comparative Example 1
[0048] The diameter of the hollow nanoparticles is selected to be 20 nm, and the addition ratio of the hollow nanoparticles is 25% by weight.
[0049] Comparative Example 2
[0050] The diameter of the hollow nanoparticles is selected to be 20 nm, and the addition ratio of the hollow nanoparticles is 55% by weight.
[0051] Comparative Example 3
[0052] The diameter of the hollow nanoparticles is selected to be 1000 nm, and the addition ratio of the hollow nanoparticles is 30% by weight.
[0053] Comparative Example 4
[0054] Hollow nanoparticles are not used, and the back coating layer uses fluorine-containing materials.
[0055] Comparative Example 5
[0056] No hollow nanoparticles are used, and general materials are used for the back coating.
[0057] The specific parameters and related performance of each embodiment are summarized in Table 1.
[0058] Table 1 Implementation parameters and performance tests of the embodiment
[0059]
[0060] Through the performance test comparison of each embodiment, it can be seen that when the hollow nanoparticles are added in a small proportion, they have a relatively high refractive index, but their hardness and wear resistance are relatively weak, and when the hollow nanoparticles are added in a large proportion, their adhesion performance is poor, and when the diameter of the hollow nanoparticles is too large, the reflectivity and haze are relatively high, which does not meet the use requirements. In addition, when fluorine-containing materials are used, the adhesion, hardness and wear resistance of the brightness enhancement film formed are relatively worse, while the refractive index of the brightness enhancement film formed by general materials is relatively high. It can be seen that when adding hollow nanoparticles, the size and weight ratio of the hollow nanoparticles need to be controlled to achieve better performance.
[0061] As can be seen from the foregoing, the present application provides an innovative and efficient brightness enhancement film design, which not only reduces production costs and improves production efficiency, but also avoids the use of environmentally harmful manufacturing methods such as fluoride and high-temperature calcination. Compared with the prior art, the brightness enhancement film of the present application achieves high brightness, high wear resistance and excellent stability through structural design and material selection. Hollow nanoparticles of specific sizes and proportions are mixed in the low refractive index coating, which can effectively reduce the reflectivity of the incident surface of the brightness enhancement film and improve the light transmittance, thereby significantly improving the brightness of the brightness enhancement film. In addition, the introduction of hollow nanoparticles also enhances the hardness and wear resistance of the back coating of the brightness enhancement film, making it more durable. In further optimized design, the present application also proposes a variety of embodiments, including an integrally formed substrate layer, coating and prism layer design, and a double prism layer structure with different prism extension directions and vertex angles, which not only improves the performance of the brightness enhancement film, but also increases the flexibility and diversity of its design. In addition, the present application further optimizes the performance and stability of the brightness enhancement film by finely controlling parameters such as the size of the hollow nanoparticles, the size of the hollow structure, and the thickness of the low refractive index coating. In particular, by gradually increasing the size of the hollow nanoparticles in the direction away from the substrate layer and coating the surface of the particles with an antistatic resin, the brightness enhancement film of the present application exhibits higher performance and longer service life. The brightness enhancement film design of the present application not only has the advantages of low cost and high efficiency, but also achieves high brightness, high wear resistance and excellent stability through a unique structure and material selection, making the brightness enhancement film of the present application have broad application prospects in display devices, lighting equipment and other fields.
[0062] The above is only a specific implementation of the present application, and any other improvements made based on the concept of the present application are deemed to be within the protection scope of the present application.
Claims
1. A brightness enhancement film, characterized in that: It comprises a first substrate layer (100), a low refractive index coating (200) and a first prism layer (300); The first prism layer (300) is arranged on the front surface of the first substrate layer (100); The low refractive index coating (200) is arranged on the back side of the first substrate layer (100); The low refractive index coating (200) is mixed with hollow nanoparticles, and the diameter of the hollow nanoparticles ranges from 20 to 500 nm.
2. The brightness enhancement film according to claim 1, characterized in that: The thickness of the low refractive index coating (200) is less than the thickness of the first substrate layer (100).
3. The brightness enhancement film according to claim 1, characterized in that: It also includes a second substrate layer (400) and a second prism layer (500), wherein the second substrate layer (400) is arranged on a surface of the first prism layer (300) opposite to the first substrate layer (100), and the second prism layer (500) is arranged on a surface of the second substrate layer (400) opposite to the first prism layer (300).
4. The brightness enhancement film according to claim 3, characterized in that: The extension direction of the prisms in the first prism layer (300) is different from the extension direction of the prisms in the second prism layer (500).
5. The brightness enhancement film according to claim 3, characterized in that: The apex angles of the prisms in the first prism layer (300) and the second prism layer (500) are 90°.
6. The brightness enhancement film according to claim 1, characterized in that: The thickness of the low refractive index coating (200) is in the range of 0.1-25 μm.
Citation Information
Cited By
Ultrathin flexible brightness enhancement film and roll-to-roll production process thereof
CN121578419A
An ultrathin flexible brightness enhancement film and a roll-to-roll production process thereof
CN121578419B
A polycarbonate glazing film and a method of making the same
CN122724071A